Factors Contributing to Violent Discipline in the Classroom: Findings From a Representative Sample of Primary School Teachers in Tanzania - Masath, Faustine Bwire (Journal of interpersonal violence, 2022)
The need for intervention strategies aiming to reduce teachers? use of violent discipline methods has been expressed repeatedly, especially for countries where this practice is socially and legally accepted. Nevertheless, initial targets for interventions are not clearly identified, as factors contributing to teachers? use of violence are still understudied. In the present study, we examined the interplay between teachers? own experiences of violence, their attitudes, current stress, and their use of violent discipline in a representative sample of 173 Tanzanian primary school teachers (53.7% female, Mage = 38.1 years, SDage = 10) using structural equation modeling. Our model showed good model fit (?2 [48, n = 173] = 78.058 (p = .004), CFI = .962, TLI = .948, RMSEA = .060 [90% CI [.034, .084], PCLOSE = .233], SRMR = .048). Results indicated direct associations between positive attitudes toward violent discipline (? = .41), stress (? = .23), and teachers? own experiences of violence (? = .21) with teachers? use of violence. Teachers? own experiences of violence were significantly associated with positive attitudes (? = .39), and these significantly mediated the association between teachers? own experiences of violence and their use of violent discipline (? =.23). Our findings underscore the relevance of past experiences, societal norms, and current working conditions in understanding teachers? violence against students. Interventions aiming to reduce teachers? use of violent discipline may focus on stress management, societal norms, personal beliefs on violent discipline, and how teachers? own previous experiences of violence may influence teacher?s disciplining behavior.